2014
DOI: 10.1039/c4fo00451e
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed extract improves epithelial structure and suppresses inflammation in ileum of IL-10-deficient mice

Abstract: Defect in intestinal epithelial structure is a critical etiological factor of several intestinal diseases such as inflammatory bowel disease. The objective of this study was to evaluate the effect of grape seed extract (GSE), which contains a mixture of polyphenols, on ileal mucosal structure and inflammation in interleukin (IL)-10-deficient mice, a common model for studying inflammatory bowel disease. Wild-type and IL-10-deficient mice were fed GSE at 0 or 1% (based on dry feed weight) for 16 weeks. GSE suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 54 publications
0
43
0
Order By: Relevance
“…In fact, GP polyphenolics quenched ROS production in Caco-2 cells bringing it lower than the control with no detrimental effect of extrusion cooking. GP polyphenolics possess antioxidant as well as anti-infla mmatory effects with a well-established health beneficial effect on intestine [9,12,45,46]. These finding suggest that GP can be used as adjunctive ingredient in the production of healthy extrusion based cornstarch expended products.…”
Section: Effect Of Gp Extrudates Extracts On Intracellular Ros Producmentioning
confidence: 80%
“…In fact, GP polyphenolics quenched ROS production in Caco-2 cells bringing it lower than the control with no detrimental effect of extrusion cooking. GP polyphenolics possess antioxidant as well as anti-infla mmatory effects with a well-established health beneficial effect on intestine [9,12,45,46]. These finding suggest that GP can be used as adjunctive ingredient in the production of healthy extrusion based cornstarch expended products.…”
Section: Effect Of Gp Extrudates Extracts On Intracellular Ros Producmentioning
confidence: 80%
“…In order to determine the variables responsible for the separation in the PCA scores, the loading plot A number of studies have been conducted aimed to evaluate various biological activities of grape seed extracts rich in polyphenolic compounds especially proanthocyanidins, e. g., antioxidant, anti-inflammatory, cardioprotective, cytotoxic, hepatoprotective. [9][10][11]17] Therefore, wine pomace and grape seeds as the dominant part of it, represent valuable source of these bioactive compounds that are used in numerous types of products in food and pharmaceutical industry. [18] Therefore, the adequate amount of raw material could be of importance implicating that one of the parameters for selecting the appropriate clone is also number of seeds per berry.…”
Section: Resultsmentioning
confidence: 99%
“…30 It has been suggested to be of use in treatment of several diseases. 31 GSE contains polyphenols including proanthocyanidins and procyanidins that showed antioxidant and free radical scavengers, being more effective than either ascorbic acid or vitamin E. 32 Their effects include the ability to increase intracellular vitamin C levels, decrease capillary permeability and fragility and scavenge oxidants and free radicals. Several studies have indicated that extracts obtained from GSE inhibit enzyme systems that are responsible for the production of free radicals.…”
Section: Discussionmentioning
confidence: 99%